2016
DOI: 10.3233/jad-150642
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular Infusion of Angiotensin-(1–7) Ameliorates Cognitive Impairment and Memory Dysfunction in a Mouse Model of Alzheimer’s Disease

Abstract: Abstract. This work was performed to test our hypothesis that angiotensin-(1-7) can ameliorate cognitive impairment and cerebrovascular reactivity in 5XFAD mice, a useful model of Alzheimer's disease. 5XFAD mice received intracerebroventricular infusion of (1) vehicle, (2) angiotensin-(1-7), or (3) angiotensin-(1-7)+A779, a specific Mas receptor antagonist, for 4 weeks. Angiotensin-(1-7), through Mas receptor, significantly ameliorated cognitive impairment in 5XFAD mice. As estimated by acetazolamide-induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…In the present study, we used 5XFAD mice because 5XFAD mice recapitulate major features of AD pathology and are regarded as 1 of the popular models of AD. [18][19][20]27 To examine spatial learning and memory function of 5XFAD mice, we used the Morris water maze test because it is the most popular behavioral assay for detecting AD-relevant cognitive impairments across species. 36,37 We found that 5XFAD mice were more prone to angiotensin II-induced cognitive impairment than control mice, as evidenced by the findings of the water maze test.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, we used 5XFAD mice because 5XFAD mice recapitulate major features of AD pathology and are regarded as 1 of the popular models of AD. [18][19][20]27 To examine spatial learning and memory function of 5XFAD mice, we used the Morris water maze test because it is the most popular behavioral assay for detecting AD-relevant cognitive impairments across species. 36,37 We found that 5XFAD mice were more prone to angiotensin II-induced cognitive impairment than control mice, as evidenced by the findings of the water maze test.…”
Section: Discussionmentioning
confidence: 99%
“…Implantation of an infusion cannula into the cerebral ventricles and an osmotic pump were performed on mice according to our previously reported method. 18 Briefly, the mice were anesthetized with 1.5% to 2% isoflurane through a face mask, and stainless steel cannulas (ALZET Brain Infusion Kit3, Durect Co, Cupertino, CA) were implanted in the right lateral ventricle, placed 1.0 mm lateral and 0.5 mm posterior from the bregma. The cannulas were fixed on the skull, and catheters were attached to extension tubes and linked to the ALZET osmotic pumps (Model 1004, Durect Co, Cupertino, CA), which were installed in subcutaneous pockets on the lateral backs of the mice.…”
Section: Implantation Of the Icv Infusion Cannula And Osmotic Pumpmentioning
confidence: 99%
See 2 more Smart Citations
“…In a mouse model of Alzheimer's disease, i.c.v. infusion of Ang(1–7) ameliorated the cognitive impairments and memory dysfunction (Uekawa et al, ). In models of Alzheimer's and Parkinson's diseases, Ang(1–7) activity correlates with tau hyperphosphorylation (Wright et al, ; Jiang et al, ).…”
Section: Experimental Model Studiesmentioning
confidence: 99%